(untitled) (Canadian Journal of Native Studies, 2026)
Using data from the Programme for the International Assessment of Adult Competencies (PIAAC), this study examined skill-job mismatches among Indigenous workers in Canada. Skill mismatches (over-skilled or under-skilled conditions) were based on direct measures of skill competencies in numeracy and literacy provided by PIAAC data. On average, Indigenous workers were more likely to be under- skilled, and less likely to be over-skilled, than their non-Indigenous counterparts. These findings may be explained by the fact that the level of education and the skill scores of Indigenous workers were significantly lower than those of non-Indigenous workers. When education was controlled, however, there were no differences in being under- or over-skilled in literacy between Indigenous and non-Indigenous workers. That is, education level played an important role in determining skill levels as well as job mismatches. Certain job-related conditions were associated with the likelihood of job mismatch among Indigenous workers. Compared to full-time workers, part-time Indigenous workers were more likely to be over-skilled; compared with employees, self-employed Indigenous workers were less likely to be under-skilled; and a higher level of skill-job mismatches were found among Indigenous workers who majored in the field of science, technology, engineering, and mathematics (STEM) in their post-secondary education than their non-STEM counterparts.